Systematic studies on a decay half-lives of neptunium isotopes. (23rd April 2021) - Zou, You-Tian; Pan, Xiao; Liu, Hong-Ming; Wu, Xi-Jun; He, Biao; Li, Xiao-Hua
Abstract: In the present work, we systematically study the α decay half-lives of neptunium ( Z = 93) isotopes within a one-parameter model (OPM). The calculated results are in reasonable agreement with the experimental data. Noticeably, the recently measured α decay half-life value of 380 − 110 + 260 ns for 222 Np [ Phys. Rev. Lett. 125, 032 502 (2020)] has been fairly reproduced by the OPM as 780 ns within a factor of ≈2. In addition, we extend this model to predict α decay half-lives of neptunium isotopes whose α decay is energetically allowed or observed but not yet quantified in NUBASE2016. Meanwhile, it is found that the half-life between the neutron number N = 126 and N = 128 in Np drop sharply, this result shows that the N = 126 shell closure is still very robust at Z = 93. At last, α particle preformation probability P α extd are extracted in two cases with α transition orbital angular momentum l = 0 and l = 1, we find a amazing phenomenon that the P α extd are basically the same for α transition with the same orbital angular momentum l .